2009
DOI: 10.1103/physrevb.80.245423
|View full text |Cite
|
Sign up to set email alerts
|

Lithium incorporation into a silica thin film: Scanning tunneling microscopy and density functional theory

Abstract: The interaction of Li with a thin silica film grown on Mo͑112͒ has been studied with low-temperature scanning tunneling microscopy ͑STM͒ and density functional theory ͑DFT͒. Thanks to the porous silica structure, single Li atoms are able to penetrate the oxide layer and bind at the metal-oxide interface. From the distinct topographic signature of the embedded atoms, the interfacial adsorption sites are determined to be along the furrows of the Mo͑112͒ surface. With increasing Li coverage, the formation of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…By varying the kind of interface defects, it is possible to tune the work function of the metal/oxide system in a desired way [13][14][15][16][17] . For examples, recent theoretical studies of doped MgO/Ag(001) interfaces, have shown that manipulating the interface by inserting oxygen or magnesium vacancies and impurities leads to an enhanced chemical reactivity of the oxide surface with respect to the catalytic dissociation of H 2 O 18 , and have further highlighted the influence of interfacial oxygen vacancies and impurities on the MgO/Ag(001) work function 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…By varying the kind of interface defects, it is possible to tune the work function of the metal/oxide system in a desired way [13][14][15][16][17] . For examples, recent theoretical studies of doped MgO/Ag(001) interfaces, have shown that manipulating the interface by inserting oxygen or magnesium vacancies and impurities leads to an enhanced chemical reactivity of the oxide surface with respect to the catalytic dissociation of H 2 O 18 , and have further highlighted the influence of interfacial oxygen vacancies and impurities on the MgO/Ag(001) work function 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These values are overestimated by about a factor two compared to experiment (for possible explanations see ref. [45]). …”
Section: Au Atom Adsorption On "Clean" and Li-doped Sio 2 / Mo(112)mentioning
confidence: 93%
“…Indeed, STM images show that the Li atoms penetrate below the silica layer and substantially lower the work function of the silica/Mo system. [44,45] The work function decrease predicted by the calculations has been deduced from the down-shift of the silica conduction band, as probed by conductance spectroscopy. [45] The Li-doped silica films have then been used to study the adsorption properties of Au atoms and clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations